2012
DOI: 10.1159/000334109
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Survival with Imatinib Mesylate Combined with Chemotherapy and Allogeneic Stem Cell Transplantation in de novo Ph+ Acute Myeloid Leukemia

Abstract: Background: De novo Philadelphia chromosome-positive (Ph+) acute myeloid leukemia (AML) is a rare disease with a poor prognosis. Imatinib mesylate (IM) is the standard treatment for Ph+ chronic myeloid leukemia and Ph+ acute lymphoblastic leukemia; however, its role in Ph+ AML has not been extensively investigated. Methods: Two patients aged of 46 and 19 years were diagnosed with de novo Ph+ AML according to the WHO Classification of Myeloid Neoplasms (2002) and the French-American-British (FAB) classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…32 Some authors have shown that Ph+ AML patients must be treated by TKIs and allo-HSCT if they are fit and have molecular or additional karyotype abnormalities resulting in a poor outcome. 12,21 Eight of 21 patients (38%) received allo-HSCT and TKIs, with Table 3). Among them, two had relapsed.…”
Section: Discussionmentioning
confidence: 99%
“…32 Some authors have shown that Ph+ AML patients must be treated by TKIs and allo-HSCT if they are fit and have molecular or additional karyotype abnormalities resulting in a poor outcome. 12,21 Eight of 21 patients (38%) received allo-HSCT and TKIs, with Table 3). Among them, two had relapsed.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (17) reported 2 patients with Ph + AML, who were treated with IM and daunorubicin-based chemotherapy, followed by allo-hematopoietic stem cell transplantation (HSCT) and IM maintenance regimen. Both patients obtained CHR and complete cytogenetic and molecular responses for 44 and 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients obtained CHR and complete cytogenetic and molecular responses for 44 and 48 months. Another patient receiving unrelated allo-HSCT during CR2, and sustained CHR for 70 months (18); therefore, IM combined with chemotherapy, followed by allo-HSCT and IM maintenance treatment appears to be an effective treatment option for Ph + AML, particularly when IM is used early (17). …”
Section: Discussionmentioning
confidence: 99%
“…Several case reports demonstrating the efficacy of tyrosine kinase inhibitors like imatinib and dasatinib towards BCR-ABL1 + AML [3,11,12,13,14,15] have been published, but there is only one report on nilotinib [16]. …”
Section: Discussionmentioning
confidence: 99%